2015
DOI: 10.1007/s11426-015-5430-x
|View full text |Cite
|
Sign up to set email alerts
|

Coil to globule transition of homo- and block-copolymer with different topological constraint and chain stiffness

Abstract: In this paper, we present the coil-to-globule (CG) transitions of homopolymers and multiblock copolymers with different topology and stiffness by using molecular dynamics with integrated tempering sampling method. The sampling method was a novel enhanced method that efficiently sampled the energy space with low computational costs. The method proved to be efficient and precise to study the structural transitions of polymer chains with complex topological constraint, which may not be easily done by using conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Hairs are chains bonded also by FENE potential with conventional parameters 45 and the harmonic bond angle potential, U b = 1 2 k bend (y À y 0 ) 2 (where k bend is the bending force constant). 47 The rigidity of the hairs is reflected by the harmonic bond angle potential, which can be varied by changing the parameter k bend . A larger k bend force parameter corresponds to more rigid hairs.…”
Section: Methods and Modelmentioning
confidence: 99%
“…Hairs are chains bonded also by FENE potential with conventional parameters 45 and the harmonic bond angle potential, U b = 1 2 k bend (y À y 0 ) 2 (where k bend is the bending force constant). 47 The rigidity of the hairs is reflected by the harmonic bond angle potential, which can be varied by changing the parameter k bend . A larger k bend force parameter corresponds to more rigid hairs.…”
Section: Methods and Modelmentioning
confidence: 99%
“…The coil-to-globule (C–G) transition is the conformational change of a single molecule and relevant to many interesting phenomena, such as the intrachain crystal nucleation, gel-network collapse, , interpolymer complexation, and even DNA or protein packing. In the monomeric solvent, Lifshitz and co-workers studied the C–G transition based on the assumption that the globule is a uniform spherical droplet with a sharp interface, , and its free energy was obtained by the ground-state dominance. The transition happens when the interfacial energy is comparable with the volume term in the core, which has a scaling behavior with the chain length as χ t r 1 / 2 N 1 1 / 2 ( b 3 / v 0 ) 1 / 2 = N 1 1 / 2 p 3 / 4 , , where p = b 2 / v 0 2/3 is the stiffness parameter ( b is the Kuhn length and v 0 is the monomer volume), and N 1 is the chain length. ,, Recently, a self-consistent field theory (SCFT) was performed to calculate the density profile of the globules, leading to the observation of swollen globule during the C–G transition and a higher solubility limit due to the formation of globules. , …”
Section: Introductionmentioning
confidence: 99%
“…In monomeric solvents, the insoluble block of the diblock copolymer in the dilute solution collapses into a compact globule as the temperature decreases, which exhibits the same coil-to-globule (C–G) transition behavior as the homopolymer. Lu and co-workers found that the topological constraint has a negligible effect on the transition point of the block copolymer. , With the increase in polymer concentration, diblock copolymers can form micelles and vesicles, where the insoluble block aggregates into a denser core, and the soluble block assembles into a shell to prevent the precipitating. …”
Section: Introductionmentioning
confidence: 99%
“…15−19 Lu and co-workers found that the topological constraint has a negligible effect on the transition point of the block copolymer. 20,21 With the increase in polymer concentration, diblock copolymers can form micelles 22−24 and vesicles, 11 where the insoluble block aggregates into a denser core, and the soluble block assembles into a shell to prevent the precipitating. 25−28 The formation of micelles was studied by Ruckenstein and Nagarajan in the framework of dilute solution thermodynamics.…”
Section: Introductionmentioning
confidence: 99%